Teknologi Informasi terhadap Kualitas Laba dengan Pengendalian Internal sebagai Variabel Pemediasi - Widya Wiradana; Oei Oei; Fransiskus E. Daromes; Kunradus Kampo (Jurnal Bisnis dan Ekonomi, 2018)
The purpose of this research was to investigate the effect of information technology on internal control, the effect of internal control on earning quality, and the role of internal control in mediating the relationship of information technology to earning quality. Population used is financial company public listed in Indonesia Stock Exchange period from 2014-2016. Number of samples are 71 firms each year, was selected by purposive sampling method and using secondary data, the annual report. The analytical method used is path analysis and hypothesis mediation analysed by using Sobel test. The result of analysis show that information technology has a positive and significant effect on internal control. Internal control has a positive and significant effect on earning quality. This research also shows that the internal control plays a role in mediate the effect of information technology disclosure on earning quality. The implication is the firms must improve information technology and five component of internal control (control environment, risk assessment, control activities, information and communication and monitoring) so that the earnings information in the financial statements of the company to be more qualified.